A study on the factors that influence the level of job satisfaction among employees at Department of Fisheries Melaka Bandaraya Bersejarah / Normah Othman and Marini Omar - Othman, Normah; Omar, Marini (Faculty of Administrative Science and Policy Studies, 2013)
Understanding the factors that influence the level of job satisfactionamong employees is vital as satisfied employees will improve overall effectiveness and successfulness of an organization while unsatisfied employees will become unproductive and eventually will decrease the performance of an organization. Department of Fisheries Melaka Bandaraya Bersejarah plays a crucial role as one of the government agency under the Ministry of Agriculture and Agro-Based Industry Malaysia (MOA Inc.) in achieving the targets outlined in the Third National Agrofood Policy (NAP, 2011 - 2020). However, a lack of attention has been focused on understanding the factors that influence the level of job satisfaction among the department’s employees. Even though the level of job satisfaction has become one of the key performance indicators (KPIs) of the department, there was no survey conducted in order to find out the results. Within 5 years, more than a dozen of employees of the department either request to be transferred, being transferred by the management, or even resigned. These grounds are reinforced by the word of mouth among employees of the department concerning their discontented feelings towards their job satisfaction. The study focused to measure the level of job satisfaction by looking from four significant factors which is leadership style, career development, and co-workers’ relationship. Thus, the main objective of this research is to study on the factors that influence the level of job satisfaction among employees at Department of Fisheries Melaka Bandaraya Bersejarah and to verify whether gender is one of the factor that influence the level of job satisfaction among employees. A questionnaire was developed and utilized to gather data regarding the importance of the factors to employees’ level of job satisfaction. Total of 39 respondents has participated in the study from the whole population of 44 employees by using simple random sampling technique. The instrument has been developed and adapted from several of previously known researches. The data gathered was statistically analyzed in order tosupport or reject the research hypotheses by using the SPSS software. The findings of the research indicated that 51 percent of the respondents agree that they are satisfied with their job. In addition, gender differences do not influence the level of job satisfaction. Limitations and recommendations on the study are also being discussed.